3 William Waller Hening, The Statutes at Large: Being a Collection of all the Laws of Virginia 205-07 (1823) - (:unkn) unknown (My University, 1701)
Provided 500-acre land grants, with the proviso that the grantee keep "upon the said land one christian man between sixteen and sixty years of age perfect of limb, able and fitt for service." Such men should be "continually provided with a well fixt musquett or fuzee, a good pistoll, sharp simeter, tomahauk and five pounds of good clean pistoll powder and twenty pounds of sizable leaden bulletts or swan or goose shott to be kept within the fort directed by this act besides the powder and shott for his necessary or usefull shooting at game..."
Keywords: MILITIAS; REQUIRED POSSESSION